ROBOTIC TEST PLATFORM - MANUKOV, IHOR; BONDARENKO, NATALIIA; BONDARENKO, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The increasingly widespread use of electrical equipment in modern life requires the construction of a platform for its testing. The article is devoted to the creation of a control system for a robotic test platform with motorized wheels and LED headlights. A structural diagram of the control system is proposed, the control principle is described and a control software is created, an element base is selected that will ensure reliable operation of the system under specified operating conditions. Due to the competent programming of microcontrollers and the correct selection of the element base, the actual problems related to the speed of operation and the reduction of the dimensions of the platform are solved. The control software is designed for use with microcontrollers of the ARM architecture of the STM32 family. The FreeRTOS operating system and specialized libraries for programming automated systems and increasing the level of abstraction were applied, which ensured modularity and portability of the code to other series of microcontrollers, facilitated testing, and greatly simplified and made the code more efficient.